Investigating the Relationship Between Cardiac Function and Insulin Sensitivity in Horses: A Pilot Study - Williams, Natasha J.; Furr, Martin; Navas de Solis, Cristobal; Campolo, Allison; Davis, Michael; Lacombe, Véronique A. (Frontiers in Veterinary Science, 2022)
Metabolic syndrome in humans is commonly associated with cardiovascular dysfunction, including atrial fibrillation and left ventricular diastolic dysfunction. Although many differences exist between human and equine metabolic syndrome, both of these conditions share some degree of insulin resistance. The aims of this pilot study were to investigate the relationship between insulin sensitivity and cardiac function. Seven horses (five mares, two geldings, aged 17.2 ± 4.2 years, weight 524 ± 73 kg) underwent insulin-modified frequently sampled intravenous glucose tolerance testing to determine insulin sensitivity (mean 2.21 ± 0.03 × 10−4 L/min/mU). Standard echocardiograms were performed on each horse, including two-dimensional, M-mode, and pulse-wave tissue Doppler imaging. Pearson and Spearman correlation analyses were used to determine the association of insulin sensitivity with echocardiographic measures of cardiac function in 5 horses. Insulin sensitivity was found to be significantly correlated with peak myocardial velocity during late diastole (r = 0.89, P = 0.0419), ratio between peak myocardial velocity in early and late diastole (r = −0.92, P = 0.0263), isovolumetric relaxation time (r = −0.97, P = 0.0072), and isovolumetric contraction time (ρ = −0.90, P = 0.0374). These preliminary data suggest that decreased insulin sensitivity is correlated with alterations in both systolic and diastolic function, as measured with tissue Doppler imaging (TDI). Due to the small sample size of this study, the relationship between insulin sensitivity and myocardial function in horses requires further investigation.